Stress level of nursing students at the clinical practicum in the University of Aguascalientes (Mexico) - De-Lira-Padilla, Griselda-Paulina; Vallín-López, Karen-Alondra; Compeán-Padilla, Violeta; Gago-Valiente, Francisco-Javier; Martins-Teixeira-da-Costa, Emilia-Isabel; Merino-Godoy, María-de-los-Ángeles (Frontiers in Education, 2025)
IntroductionCoping with stress is a process that involves a particular relationship between the individual and his/her environment. Nursing students are exposed to stressful situations during their practical training, due to the responsibilities they take, which increase as they pass the semesters. The aim of this study was to identify the stress level in the clinical practicum of nursing students at the Autonomous University of Aguascalientes (UAA) (Mexico) in each semester, taking into account a series of sociodemographic variables.MethodsThis study employs a quantitative, correlational, and comparative design with a non-experimental, cross-sectional approach. The sample consisted of 190 nursing students belonging to different semesters of the clinical practicum of the UAA. The KEZKAK instrument was used to gather data.ResultsModerate to high stress levels were reported by 70.2% of the participants, indicating a considerable prevalence of stress among the sample. With regard to the association of stress levels with each semester, it was observed that the seventh semester obtained the highest percentage of stress, with statistically significant differences (p < 0.001). Female students also reported higher stress levels than male students, although this difference was not statistically significant (p = 0.428).DiscussionNursing students in the clinical practicum have moderate stress levels. The clinical practicum represents a transmission of knowledge that will help students to become professionals. Therefore, in order to fulfill their main goal of providing care to others, nursing students must take care of their own health.